THE PEDAGOGICAL AND PSYCHOLOGICAL CHARACTERISTICS OF DEVELOPING STUDENTS’ PROFESSIONAL COMPETENCE THROUGH AN INDIVIDUAL APPROACH (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article analyzes the pedagogical and psychological characteristics of developing students’ professional competence based on an individual approach. It highlights methodological strategies aimed at fostering a learner-centered approach in training future specialists, enhancing cognitive and creative potential, and strengthening motivation and reflection. The paper also explores effective ways to develop professional competence using modern educational technologies, digital tools, and psychological-pedagogical factors. Competencies formed through the integration of social aspirations, professional inclinations, and values are examined. The article offers recommendations for identifying the key factors of professional preparation and applying them in pedagogical practice.